2002 genel seçimlerinde Edirne yerel gazetelerinin siyasal iletişimdeki rolü - Bozkurt, Hale (My University, 2006)
Siyasal iletişim aktörlerinden siyasi partilerin ve milletvekili adaylarının 2002 Genel Seçimlerinde Edirne’de yerel gazeteleri kullanırken izledikleri siyasal pazarlama yollarını araştıran, gazeteler ve siyasal iletişim sisteminin birbirleriyle olan ilintisini irdeleyen ve bu alanlardaki dönüşümleri gözler önüne seren bu tez çalışması gazetelerin de siyasal iletişim açısından tavırlarını belirler. Çalışmanın asıl konusu; bu alanlarda yaşanan dönüşümleri ve günümüzde gelinen noktaları belirledikten sonra siyasetin nasıl yapıldığı, siyasal pazarlamanın siyasi partilerde nasıl kullanıldığı ve Kasım 2002 seçimleri öncesinde Edirne merkezindeki, Hudut, Sonhaber, Edirne, Edirne Haber, Vatandaş Gazeteleri’nin haberlerinin siyasal pazarlama iletişimi açısından araştırılmasıdır. Araştırma sonuçları Edirne yerel gazetelerinin taraflı bir habercilik içinde olduğunu göstermektedir. Edirne’deki yerel gazeteler seçim döneminde siyasal aktörler ve seçmenler arasındaki iletişimi dengeli bir biçimde sağlayamamıştır. Sahiplik öğesi ve reklam gelirlerine bağlı lehte bir yayıncılık anlayışı benimsemiştir. Ancak, siyasal aktörler tarafından kullanılan yerel gazetelerin seçmen üzerinde herhangi bir etkisi de oluşmamıştır.

THE ROLE OF THE LOCAL PAPERS IN EDIRNE IN POLITICAL COMMUNICATION IN 2002 GENERAL ELECTION This thesis study, which searches the political marketing strategies followed by the political parties and candidates for Member of Parliament - the elements of political communication actors - when they used the local papers as a tool in 2002 General Election, considers the relationship with the local papers and political communication system between each other and shows the conversions in these fields, also determines the attitudes considering the political communication of the local papers. The main subjects of this study are how to make politics after determining the conversions of this field and how it came to the present day, how political marketing are used in the political parties and to search local papers located at the centre such as; Hudut, Sonhaber, Edirne, Edirne Haber, Vatandaş considering the political marketing communication before November 2002 General Election. The results of the research show that the local papers of Edirne are in the mood of unfair journalism. The local papers in Edirne could not provide the communication between the political actors and voters in harmony during campaign. They tended to embrace a concept, an understanding of beneficiary publishing (style) depending on advertisement incomes and having ownership in the local papers. On the other hand, any kind of impact of the local papers, which are used by the political actors, has not been formed on voters.
Keywords: Gazetecilik; Yerel Basın_Siyaset ve Yönetim